Evaluating the complementarity of knowledge and psychosocial risk management to improve employee well-being and performance through improved work organisation and management - Fadipe, Tolulope G. (2019)
The ever-changing economic and social environments, and technological advancements have resulted in significant changes to the world of work. These changes have led to growing recognition that to be sustainable, organisations must promote a positive psychosocial work environment (PWE). A number of approaches have been developed to improve business sustainability and maximise organisational performance, two among these include Knowledge Management (KM) and Psychosocial Risk Management (PRM). Various Psychosocial Risk Management (PRM) initiatives have been developed to enable organisations to control psychosocial risks (associated with aspects of work organisation, design and management that have the potential to cause various negative outcomes to employees and organisations) at source where possible or minimise their negative impact. On the other hand, the Knowledge Management (KM) concept was introduced for organisational competitiveness and economic growth, and aims to achieve these objectives through also addressing aspects of work organisation, design and management.